"Particles‐to‐People…Molecules‐to‐Man": Creationist Poetics in Public Debates. (13th May 2019) - Bielo, James S.
Abstract : This article examines religious language in a contested public sphere by analyzing performances of linguistic creativity among creationists in the United States. The public creation‐evolution debate has been a central speech event in the development of modern creationism, and functions as a key site for claiming cultural legitimacy. Focusing on three creation‐evolution debates spanning 33 years, I advance the concept of "creationist poetics" to capture how framing, stance taking, and speech play define the performance repertoire of creationists in the debate context. In particular, I illustrate how creationist speakers work to create a conspiracy‐populist frame and a revealer stance. Together, these strategies sketch a lifeworld that envisions elitist "secular" actors suppressing scriptural authority and creationists as humble, clear‐eyed people exposing the conspiracy through scriptural fidelity. I argue that this system of poetics is a key expressive resource in the ongoing struggle to wrest authority away from evolutionary science and claim it for biblical fundamentalism. Ultimately, this analysis of creationist poetics informs our understanding of how authority as a contingent social process is discursively mediated, a central theme in the study of both religious and political language.